Bioactive Compounds of Citrus Fruits: A Review of Composition and Health Benefits of Carotenoids, Flavonoids, Limonoids, and Terpenes - Ramesh Kumar Saini; Arina Ranjit; Kavita Sharma; Parchuri Prasad; Xiaomin Shang; Karekal Girinur Mallikarjuna Gowda; Young-Soo Keum (MDPI AG, 2022)
The increased consumption of fruits, vegetables, and whole grains contributes to the reduced risk of many diseases related to metabolic syndrome, including neurodegenerative diseases, cardiovascular disease (CVD), diabetes, and cancer. Citrus, the genus Citrus L., is one of the most important fruit crops, rich in carotenoids, flavonoids, terpenes, limonoids, and many other bioactive compounds of nutritional and nutraceutical value. Moreover, polymethoxylated flavones (PMFs), a unique class of bioactive flavonoids, abundantly occur in citrus fruits. In addition, citrus essential oil, rich in limonoids and terpenes, is an economically important product due to its potent antioxidant, antimicrobial, and flavoring properties. Mechanistic, observational, and intervention studies have demonstrated the health benefits of citrus bioactives in minimizing the risk of metabolic syndrome. This review provides a comprehensive view of the composition of carotenoids, flavonoids, terpenes, and limonoids of citrus fruits and their associated health benefits.